2009
DOI: 10.1063/1.3072033
|View full text |Cite
|
Sign up to set email alerts
|

Calculated electronic and magnetic structure of rutile phase V1−xCrxO2

Abstract: Recent experiments indicate that films of V1−xCrxO2 may be obtained which retain the tetragonal rutile phase to low temperature. In order to better understand this system we have calculated its electronic structure using density functional theory in the generalized gradient approximation and density functional theory with empirical on-site Coulomb correlations (LDA+U). Within these approximations we find that the ground state of rutile phase V1−xCrxO2 is quite simple. Both V and Cr are in the +4 state, implyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The obtained total energies of spin-polarized (FM and AFM) states are always lower than that of the spincompensated PM state. For example, Williams et al [57] have calculated the energy differences of R-VO 2 in magnetic states (AFM and FM) with respect to the non-spin polarized state. It was found that the energies of FM and AFM phases are lowered by 135 meV/ VO 2 and 56 meV/VO 2 using the PBE GGA, compared to the non-spin-polarized phase.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained total energies of spin-polarized (FM and AFM) states are always lower than that of the spincompensated PM state. For example, Williams et al [57] have calculated the energy differences of R-VO 2 in magnetic states (AFM and FM) with respect to the non-spin polarized state. It was found that the energies of FM and AFM phases are lowered by 135 meV/ VO 2 and 56 meV/VO 2 using the PBE GGA, compared to the non-spin-polarized phase.…”
Section: Computational Detailsmentioning
confidence: 99%
“…One should note that, in the works of Williams and coworkers [57], both the lattice constants and atomic positions were fixed to their experimental values. However, the atomic positions are allowed to relax in our calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In order to understand the effects of vanadium substitution on CrO 2 [15], which both predicted a half-metallic FM ground state. The initial calculations were performed in simple six-atom rutile cells with the experimental crystal structure (Ref.…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, thin films grown on a (001) Al 2 O 3 substrate are stable in the rutile phase down to 100 K, and the semiconductor-insulator transition is suppressed [17,19]. DFT calculations by Williams et al [15] predicted these stabilized rutile V x Cr 1−x O 2 compounds to be not only ferromagnetic, but also half-metallic. Nevertheless, a later experimental study revealed V 0.82 Cr 0.18 O 2 to be a ferromagnetic insulator [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation